A literature review on pharmacologic therapy for abdominal aortic aneurysms - Romão Rodrigues, Marta (2023)
Aortic aneurysms affect 3.3% of adults and there is a growing burden of small aneurysms detected, which may grow to need surgical repair. Still, we rely only on surgical therapy for this disease, left to monitor patients until they are candidates for treatment. Pharmacologic therapies have long been proposed and studied and still we have no evidence supporting drug therapy in small aneurysms. In this report we make a narrative review of basic molecular aspects of aneurysm disease and of evidence behind drug therapies that have been proposed and studied throughout the last decades.